Attaining the 2030 Sustainable Development Goal of No Poverty - Birdthistle, Naomi (Family businesses on a mission., 2024)
Attaining the 2030 Sustainable Development Goal of No Poverty focuses on Sustainable Development Goal number one (SDG#1): to end poverty in all its forms everywhere. Examining family businesses in the UAE, Lebanon, India, Zambia, and England, each chapter case study presents a unique perspective from their respective country. The case studies presented generate insights and key takeaways into the role of family businesses in ending poverty and tackling its growing inequality detrimental to economic growth, social cohesion, stability, and peace. The United Nations' (UN) Sustainable Development Goals (SDGs) are 17 Goals pledged by 193 nations in 2015 which would help engender an improved, fairer, and more sustainable world - one in which 'no one is left behind'. The SDGs are a call to action, to develop innovative solutions to the most complex, societal, and environmental global challenges. In Family Businesses on a Mission, series editor Naomi Birdthistle brings together international case studies to illustrate how family businesses can attain the UN 2030 SDGs. Accessible to those working in the field beyond academia - such as family business practitioners, family business owners, government and policymakers, members of NGOs, business associations and philanthropic centres - this book series equally appeals to those with a general interest in entrepreneurship and business.